2017
DOI: 10.1017/jfm.2017.228
|View full text |Cite
|
Sign up to set email alerts
|

Transition and turbulence in horizontal convection: linear stability analysis

Abstract: The linear instability mechanisms of horizontal convection in a rectangular cavity forced by a horizontal buoyancy gradient along its surface are investigated using local and global stability analyses for a Prandtl number equal to unity. The results show that the stability of the base flow, a steady circulation characterized by a narrow descending plume and a broad upwelling region, depends on the Rayleigh number, $Ra$. For free-slip boundary conditions at a critical value of $Ra\approx 2\times 10^{7}$, the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
3
13
0
Order By: Relevance
“…At higher Ra, plumes will detach faster, and for sufficiently large Ra one finds multiple plumes detaching from the thermal BL. This phenomenon was reported in Passaggia et al (2017) for Ra = 9 × 10 14 , where plumes were visible immediately after entering the convectively unstable region.…”
Section: Plumessupporting
confidence: 67%
See 1 more Smart Citation
“…At higher Ra, plumes will detach faster, and for sufficiently large Ra one finds multiple plumes detaching from the thermal BL. This phenomenon was reported in Passaggia et al (2017) for Ra = 9 × 10 14 , where plumes were visible immediately after entering the convectively unstable region.…”
Section: Plumessupporting
confidence: 67%
“…Gayen et al (2014) showed, for Pr = 5 and varying Ra, that the flow goes through a sequence of stability transitions, starting with the growth of plumes in the BL, followed by convective rolls at higher Ra, and finally show fully 3-D turbulence within a region above the hot BL at Ra ≈ 5 × 10 11 . The linear stability analysis of Passaggia, Scotti & White (2017) for Pr = 1 supports these findings and suggests that there exists a competition between 3-D rolls around a streamwise axis and two-dimensional (2-D) Rayleigh-Taylor (RT) instability. The former seem to be dominant in wider cells, as found by Sukhanovsky et al (2012), whereas the latter seems to be most relevant for no-slip BC in narrow cells.…”
Section: Dynamics: Plumes and Oscillationsmentioning
confidence: 68%
“…(3.10) (Shishkina, Grossmann & Lohse 2016;Passaggia, Scotti & White 2017). The advantage of the profile (3.10) is that the horizontal buoyancy flux through the discontinuity in b s (x) -that is J(0) -is distinguished and provides a 'natural' definition of the horizontal-convective Nusselt number.…”
Section: The Nusselt Number Nu Defmentioning
confidence: 99%
“…At early times, the dye travels from the fresh side in a laminar and stratified layer toward the salty side where it sinks as a turbulent plume [see Figs. 1(a)-1(f)] [2]. The bottom of the tank is progressively filled with dyed/salty water which has mixed in the plume and drives a deep circulation [see Fig.…”
mentioning
confidence: 99%